Hybrid Intrusion Detection Architecture for Cloud Environment (International Journal of Engineering and Computer Science, 2015)
The Cloud computing system can be easily threatened by various attacks, because most of the cloud computing systems provide service to so many people who are not proven to be trustworthy. Due to their distributed nature, cloud computing environment are easy targets for intruders[1]. Intrusions have been a major problem in terms of computing resources such as grid computing, ubiquitous computing ,cloud computing, distributed computing and so on. Intrusions are hard to detect but there has been a lot of work done on detecting and removing the intrusions .The focus of intrusion detection should be mainly on detecting the intrusions at the system resources and at the network level for a predefined network. In this paper we proposed a system is to detect intrusions in the cloud computing using  Behavior-based approach and knowledge-based approach. If first approach unable to detect the data, second approach again verifies the data and compare it with the signatures within the database. In the proposed system definitely we will have very low false positive alarm.  This paper surveys the intrusion detection and prevention techniques and possible solutions in Host Based and Network Based Intrusion Detection System. Different Intrusion Detection techniques are also discussed namely anomaly based techniques and signature based techniques. It also surveys different approaches of Intrusion Prevention System.